PENINGKATAN PRODUKTIVITAS LAHAN MELALUI PEMANFAATAN LAHAN PERKARANGAN DI MEUREUBO KABUPATEN ACEH BARAT - Irvan Subandar; Diswandi Nurba; Abdul Gafur (Universitas Teuku Umar, 2018)
Food security is the principal problem in most countries in the world. One of the efforts to build food security of families through land use lawns that are beneficial in supporting the family in addition to nutritional needs at once to beauty (aesthetics) when optimally managed and planned. Land can be developed as an area of the Kawasan Rumah Pangan Lestari (KRPL). This activity is conducted in Gampong Ujong Tanoh darat and Gampong Pasi Aceh Baroh Sub-district Meureubo, Aceh Barat. The selection of the location based on the consideration that location most of the inhabitants are farmers. The second reason is expected to give direct benefits of the existence of the Agriculture Faculty Of Teuku Umar University in the middle of the community. The third reason is to expect the gampong can become Small-scale Agriculture Faculty Of Teuku Umar University. The outer achievedare KRPL product andnursery. The outer of services are the achievement of self-reliance and material management of the farming community. The implementation of the activities carried out have been completed, KRPL vertikultur model, nursery, outreach to the community, and technical guidance to the community gampong. The success rate of the program was can be known the desire ofcommunity especially the housewife, prevail in their house by making use of the potential of the existing yards, though not exactly the same as the model that is applied. Keyword: Food Security, KRPL, Land, Vertikultur